Pendekatan Game dalam Program Latihan untuk Meningkatkan Passing Bawah Atlet Bola Voli - Hakim, Hikmad; Ishak, Muhammad; Awaluddin (Jurnal Keolahragaan JUARA, 2025)
This study aims to test the effectiveness of the game-based training approach in improving the underhand passing ability of adolescent volleyball athletes at the Syekh Yusuf Gowa Club. The method used is a quasi-experimental study with a pre-test and post-test design and a control and experimental group. The sample consisted of 20 athletes who were divided by purposive sampling into two groups, each consisting of 10 people. The experimental group underwent training with a game-based approach for 8 weeks, 3 times a week, while the control group used conventional training methods. The results showed that the experimental group experienced an average increase in underhand passing scores of 14.2 points, while the control group only increased by 5.2 points. The Paired Sample t-Test showed a significant increase in both groups (p <0.05), but the increase in the experimental group was significantly greater than the control group based on the Independent Sample t-Test (p <0.05). The normality and homogeneity tests of the data showed that the assumptions were met so that the statistical analysis was valid. This study concludes that the game-based training approach is effective in improving underhand passing skills in adolescent volleyball athletes and is recommended for use in athlete development.